PARTISIPASI ANGGOTA DALAM AKTIVITAS HONDA STREET FIRE CLUB INDONESIA (HSFCI) DI KOTA PEKANBARU - Aditia Rahman Nugraha; Indrawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research is done in Pekanbaru City. With the formulation of the problem (1) how the characteristics of members who are members of Honda Street Fire Club Indonesia (HSFCI) Pekanbaru? (2) what is the level of participation of members in the activities of Honda Street Fire Club Indonesia (HSFCI) Pekanbaru ?. The purpose of this study is to determine the characteristics of members who are members of Honda Street Fire Club Indonesia (HSFCI) Pekanbaru? To know the level of participation of members in the activities of Honda Street Fire Club Indonesia (HSFCI) Pekanbaru ?. This research is a descriptive research with quantitative approach. The population in this study as much as 45 people then in use one of the sampling technique by census or whole then in get sampel as much as 45 people, to collect data of this research in use questioner and documentation. Based on the results of the research can be concluded that (1) Members who are members of the motor community of Honda Street Fire Club Indonesia (HSFCI) Pekanbaru have a high characteristic to the characteristics of Honda Street Fire Club Indonesia (HSFCI) Pekanbaru. (2) HSFCI member participation has three factors influencing the high, medium and low participation of members of Honda Street Fire Club Indonesia (HSFCI) Pekanbaru. Keywords: Characteristics, Participation